Spatiotemporal dissemination of ESBL-producing Enterobacterales in municipal sewer systems: a prospective, longitudinal study in the city of Basel, Switzerland - Gómez-Sanz, Elena; Bagutti, Claudia; Roth, Jan A.; Alt Hug, Monica; García-Martín, Ana B.; Maurer Pekerman, Laura; Schindler, Ruth; Furger, Reto; Eichenberger, Lucas; Steffen, Ingrid; Egli, Adrian; Hübner, Philipp; et al. (Frontiers in Microbiology, 2023)
Background: The contribution of community and hospital sources to the transmission of extended-spectrum β-lactamase producing Enterobacterales (ESBL-PE) remains elusive. Aim: To investigate the extent of community dissemination and the contribution of hospitals to the spread of ESBL-PE by exploring their spatiotemporal distribution in municipal wastewater of a central European city. Methods: Wastewater samples were collected monthly for two consecutive years throughout Basel, Switzerland, including 21 sites across ten postcode areas of the city collecting either community wastewater (urban sites, n=17) or community and hospital wastewater (mixed sites, n=4). Presumptive ESBL-PE were recovered by selective culture methods. Standard methodologies were applied for species identification, ESBL-confirmation, and quantification. Results: Ninety-five percent (477/504) of samples were positive for ESBL-PE. Among these isolates, Escherichia coli (85%, 1140/1334) and Klebsiella pneumoniae (11%, 153/1334) were most common. They were recovered throughout the sampling period from all postcodes, with E. coli consistently predominating. The proportion of K. pneumoniae isolates was higher in wastewater samples from mixed sites as compared to samples from urban sites, while the proportion of E. coli was higher in samples from urban sites (p=0.003). Higher numbers of colony forming units (CFUs) were recovered from mixed as compared to urban sites (median 3.2x102 versus 1.6x102 CFU/ml). E. coli-counts showed moderate correlation with population size (rho=0.44), while this correlation was weak for other ESBL-PE (rho=0.21). Conclusions: ESBL-PE are widely spread in municipal wastewater supporting that community sources are important reservoirs entertaining the spread of ESBL-PE. Hospital-influenced abundance of ESBL-PE appears to be species dependent.